Analysis Of Plant Vegetation In The Forest Park Of Langsa City - Khairul Alfi Syahra; Hasanuddin Hasanuddin; Wardiah Wardiah; Samingan Samingan; Dewi Andayani (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2021)
ABSTRACTLangsa City Forest is a green open area that is used as a tourist spot and is an open laboratory. One aspect that can be used as an open laboratory benchmark is the amount of vegetation species in an urban forest park. ‘`This study aims to determine the species, important value index (INP), and the level of diversity in Langsa City Forest Park. The` research was conducted in October 2020 - January 2021. The data were taken by dividing three observation station points. The objects of this research were all plant species with tree, shrub, shrubs, and herbs with a tree plot size of 10m x 10m, a bush / shrub plot of 5m x5m, and a herb plot of 1m x 1m. The research parameters were species, frequency, density, and species density in each habitus, and supporting environmental parameters including temperature, soil pH, light intensity, humidity (soil air). `Data analysis was performed using the Shannon-wienner diversity index formula. The results` obtained 60 plant species consisting of tree species (33 species), shrubs (6 species), shrubs (11 species), and herbs (8 species). The species that dominates the Langsa City Forest Area is Damar (Agathis dammara Lamb.Rich.) (INP = 36.80%) and the level of vegetation diversity is categorized as high (H '= 3.86).Keywords: vegetation, important value, urban forest Hutan Kota Langsa merupakan ruang terbuka hijau yang dijadikan tempat wisata dan merupakan laboratorium terbuka. Salah satu aspek yang dapat menjadi tolak ukur laboratorium terbuka adalah jumlah vegetasi spesies pada sebuah taman hutan kota. Penelitian ini bertujuan untuk mengetahui spesies, indeks nilai penting (INP), dan tingkat keanekaragaman di Taman Hutan Kota Langsa. Penelitian dilakukan pada bulan Oktober 2020 – Januari 2021. Data diambil dengan membagi tiga titik stasiun pengamatan. Objek penelitian ini yaitu seluruh jenis tumbuhan yang berhabitus pohon,semak, perdu, dan herba dengan ukuran plot untuk pohon yaitu 10m x 10m, plot semak/perdu yaitu 5m x5m, dan plot herba yaitu 1m x 1m. Parameter penelitian yaitu  spesies, frekuensi, kerapatan, dan kerimbunan spesies pada masing-masing habitus, dan parameter lingkungan pendukung meliputi suhu, pH tanah, intensitas cahaya, kelembaban (tanah udara). Analisis data yang dilakukan menggunakan rumus indeks keanekaragaman Shannon-wienner. Hasil penelitian diperoleh 60 spesies tumbuhan yang terdiri dari spesies berhabitus pohon (36 spesies), semak (6 spesies), perdu (11 spesies), dan herba ( 8 spesies). Spesies yang mendominasi Kawasan Hutan Kota Langsa adalah Damar (Agathis dammara Lamb.Rich.) (INP=36,80%) dan tingkat keanekaragaman vegetasi dikategorikan tingg (H’=3,86)Kata kunci: keanekaragaman, vegetasi, nilai penting, hutan kota